A szőlészet és borászat helyzete az 1990-es években - Bodnár, László (Tér és Társadalom, 1996)
Nowadays we can witness a rearrangement process in the field of wine-growing and wine-producing. One of the reasons is the significant slackening of market possibilities, and also the growing quality requirements. The mistakes, unclassified questions of profit-process become more and more acute. Exportation-centredress of wine-producing should remain, it is of great importance. It can be realized through a more standardized requirement-system in the field of both foreign and home Trade ensure this we need a fixed production basis, carefully elaborated concepts concerning our activity in the foreign market. Sooner our exportation was characterized by a one-channel sale-system. Nowadays, however, wine is délivered to the foreign market by more trade and exporting companies. The development of wine-growing and wine-producing, which could meet the necessary demands, is possible in perspective only. The present situation, on the one hand, defines the next measures, but in the perspective, on the other hand, it also limitations the size and pace of the development. To restore the harmony between production and consumption, to make distorted price and value relations meet market value standards, to privide a profitable production on ground of utilizing oecological, biological and technological reserves, to validate the points of view of origin, naming and quality-loyalty in the product-structure are urgent tasks in the field of wine-producing. We need differentiated consumer prices in the cóuntry which would be in harmony with consumption prices and solvent demands. The exportation orientated character of wine-producing requires grounded foreign trade activity.